Letter : Wencaslao Carrillo - McKenna, Tom
026-0025-001 International Metalworkers' Federation Established 1893 International Secretary: CONRAD ILG. Berne, Switzerland. BRITISH SECTION Hon. Secretary: THOMAS MCKENNA. O.B.E. Phone 2961 93 Borough Road W., Middlesborough. 12th August, 1939. Sir Walter Citrine. Trades Union Congress. Transport House, Smith Square, LONDON. S.W.1. Dear Sir Walter Citrine, Wencaslao Carrillo. I sent you a letter with reference to the above on July 31st; so far I have received no acknowledgement. I am anxious to know if it reached you. Will you please let me know. Yours sincerely, Thomas McKenna 292/946/26/25